Determines of US banks’ profitability and the global financial crisis - Zhang, Lingfei (2019)
The aim of this dissertation is to analyse the determinants of the US banks’ profitability of 98 US banks listed by total assets of 2018. This paper introduces the causes of the financial crisis and the changes of the US banking industry after the global financial crisis (GFC). Giving a literature review about banks’ profitability, efficiency, macroeconomy and Trump’s economic view. This paper also analysis and discuss the changes in the US banking industry after GFC through market structure and etc. With the help of GMM, this dissertation discusses the influence of both macroeconomic variables (GDPGR, INF and UNEMP) and bank specific variables (Size, Liquidity, Credit risk, Efficiency, capitalization and Risk taking) on banks profitability. This paper concludes that GDPGR, LN TA, LLRGL have positive effects on banks’ profitability when INF, UNEMP, LN TA2, LIQ, COST, CRE, Z-Score are negative.